Mortality in the developing world- Can pharmacists intervene? - I, Patel; J, Chang; J, Srivastava; R, Balkrishnan (Indian Journal of Pharmacy Practice)
The ever mounting challenge facing global health today is the wide spread gap between the life expectancy observed in the developed and the developing world. War, famine, communicable and non-communicable diseases challenge sustainable development of the human health in rd the impoverished 3 world nations. Mortality of the population is mainly influenced by the economic, social and technological advances taking place in a nation. In contrast to the healthy lives enjoyed by the inhabitants of Monaco with a highest life expectancy of 90 years, people of Swaziland experience a life expectancy of only 32 years which is the lowest in the world. A majority of the people in the developing nations fall prey to life threatening diseases and infections. This paper provides a comprehensive summary of the causes of mortality among children, adults and older adults across different continents. Independent pharmacies in developing nations can play an important role in reducing mortality, providing continuity of care, improving life expectancy and public health in areas where high health disparity exists. Personalization provided by the pharmacists can improve medication adherence, identify health needs and inspire people to improve their health.
Keywords: mortality trends; life expectancy; WHO; global health; developing nations